Postprandial rise of essential amino acids is impaired during critical illness and unrelated to small‐intestinal function. Issue 1 (6th May 2021) - van Gassel, Rob J. J.; van de Poll, Marcel C. G.; Schaap, Frank G.; Plummer, Mark; Deane, Adam; Olde Damink, Steven W. M.
Abstract: Background: Postprandial rise of plasma essential amino acids (EAAs) determines the anabolic effect of dietary protein. Disturbed gastrointestinal function could impair the anabolic response in critically ill patients. Aim was to investigate the postprandial EAA response in critically ill patients and its relation to small‐intestinal function. Methods: Twenty‐one mechanically ventilated patients and 9 healthy controls received a bolus containing 100 ml of a formula feed (Ensure) and 2 g of 3‐O‐Methyl‐d‐glucose (3‐OMG) via postpyloric feeding tube. Fasting and postprandial plasma concentrations of EAAs, 3‐OMG, total bile salts, and the gut‐released hormone fibroblast growth factor 19 (FGF19) were measured over a 4‐hour period. Changes over time and between groups were assessed with linear mixed‐effects analysis. Early (0–60 minutes) and total postprandial responses are summarized as the incremental area under the curve (iAUC). Results: At baseline, fasting EAA levels were similar in both groups: 1181 (1055–1276) vs 1150 (1065–1334) μmol·L−1, P = .87. The early postprandial rise in EAA was not apparent in critically ill patients compared with healthy controls (iAUC60, −4858 [−6859 to 2886] vs 5406 [3099–16, 853] µmol·L −1 ·60 minutes; P = .039). Impaired EAA response did not correlate with impaired 3‐OMG response (Spearman ρ 0.32, P = .09). There was a limited increase in total bile salts but no relevant FGF19 response in either group. Conclusion: Postprandial rise of EAA is blunted in critically ill patients and unrelated to glucose absorption measured with 3‐OMG. Future studies should aim to delineate governing mechanisms of macronutrient malabsorption.